Membangun Resiliensi ‘I Have’ Mantan Anak Binaan Melalui Supplemental Family: Studi Pada Program Transition Home Di Free and Safe Indonesia Foundation - Resti Kinanti Sekarsari; Maulana Irfan; Lenny Meilany (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Negeri Balikpapan., 2026)
This study aims to analyze how social institutions fulfill the role of a “supplemental family” in providing the “I Have” source of resilience for former juvenile offenders who are beneficiaries of the Transition Home Program at the Free and Safe Indonesia Foundation. “I Have” is a source of resilience referring to external support. This study employs a phenomenological approach to understand the experiences of former juvenile offenders in perceiving the Free and Safe Indonesia Foundation as a source of support during the process of social reintegration. Data were collected through interviews, observation, literature review, and document analysis involving two main informants and three supporting informants. Data analysis was conducted thematically, drawing on the five elements of the ‘I Have’ resilience framework. The research findings indicate that the Free and Safe Indonesia Foundation functions as a supplemental family—specifically, a type of voluntary kin that complements the role of the biological family, which remains present but cannot function optimally—by fulfilling the five elements of the “I Have” sources of resilience: trusting relationship, structure and rules at home, role models, encouragement to be autonomous, and access to services. The research findings indicate that the relationship formed between beneficiaries and the Transition Home environment is no longer perceived as a formal service relationship, but rather as a familial bond that provides a sense of belonging, a sense of ownership, and sustains social support. This study confirms that social institutions can serve as a legitimate source of ‘I Have’ resilience for former juvenile offenders and contribute to the process of social reintegration through an approach based on relationships and a sense of community.